Some biological activities of Malaysian leech salive extract - M.Abdualkader, Abdualrahman; Merzouk, Ahmed; Mohammed Ghawi, Abbas; Alaama, Mohammed (IIUM Press, 2011)
Leeches were fed on the phagostimulatory solution through parafilm membrane. The satiated leeches were forced to regurgitate the solution by soaking them in an ice-container. The anticoagulant activity was ascertained using thrombin time assay (TT). The result revealed that the saliva concentration which increases TT by 100% (IC100) is 43.205 μg/ml plasma. The antimicrobial activity of the saliva was tested against several bacterial spp. (E. coli, P. aeruginosa, B. cereus, Sal. typhi and S. aureus) and fungi spp. (C.albicans and C.neoformans). It was found that saliva has an inhibition activity against Sal. typhi (minimal inhibitory concentration MIC 78.253 μg/ml), S.aureus (MIC 78.253 μg/ml) and E .coli (MIC 121.256 μg/ml).